(3GdGYJHGQ aj GdfGSN hGdefShN aj GdMOjKs - (3eMeO Hf ehSi Hf YKeGf GHf MGRe, CHh HcQ, Rjf GdOjf, GdeYQha HGdMGRej,J (B584 (3g` s ((3eMeO Hf UObI GdhGSWi s)
(3ChdgG (B:s
(3bGd GdTjN GdCLd GdMGaX Rjf GdOjf GdMeO ddg GdcHjQ GdeJYGd GdcKjQ GdfhGd CeG HYO agPG cJGH GPcQ ajg eG GfJgJ Edi eYQaJg ef fGSN MOjK QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3aEPG CWjY QShd Gddg Udi Gddg Ydjg hSde abO CWjY Gddg JYGdi BNQg HJeGeg Je LejY GdOjhGf hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3QhGjI GdTjN CHj ESMGb GHQGgje Hf YeQ Hf Ydi Hf SeGbG GdETYQhi HNW ajg HYV GdebGHdIs
(3cJHJ Yf fSNI HNW GdeUfas
(3HBNQgG UhQI SeGY ef GdCUd Gdefbhd Yfg HNW GdeUfa hfSNJG ebGHdI hHChdgG agQS HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdMOjK h GdeUWdMs